The Animation Show of Shows - Volume 18 - Yamamura, Koji; Condie, Richard; Schwizgebel, Georges (Acme Filmworks, 2007)
Since 1998, "The Animation Show of Shows" has selected the best in animated short films from the world's most renowned animation festivals and presented them at the major animation studios to inspire their animators and directors. Now for the first time, the films featured in "The Animation Show of Shows" are available in this special DVD collection along with some of the most memorable animated short films of all time. [Cover]